The objectives of Sharia according to Sheikh Muhammad Al-Khal, as presented in his book (The Philosophy of the Islamic Religion) - Saleh, Prof. Dr. Aras Muhammad (Sulaimani Journal for Humanities, 2023)
This research deals with the objectives of the Islamic religion from the perspective of Sheikh Muhammad Al-Khal, and this is through his book (Philosophy of the Islamic Religion), which was published in 1939 AD, in which the writer briefly discusses the objectives of Islamic law. In the second section, the researcher talks about the purposes of faith and its pillars from the perspective of Sheikh Muhammad Al-Khal, then addresses the purposes of worship and their effects on the individual and society, and explains the ruling and purposes of prayer, zakat, fasting, and Hajj in the thought of Sheikh Muhammad Al-Khal. The research also addresses the purposes of the penal provisions in Islam, explains the philosophy of the impact of implementing these provisions on society, and explains that these punishments were enacted to deter and rebuke, so that public and private life would not be disrupted due to the spread of crimes as a result of the perpetrators avoiding punishment. Finally, it examines the purposes of justice and consultation in Islam, explains the role of justice in society, and the importance of practicing consultation in public and private affairs.
Keywords: Purposes; Islam; Sheikh Mohammed Khal